Improved Energy Efficient Anytime Optimistic Algorithm for PEGASIS to Extend Network Lifetime in Homogeneous and Heterogeneous Networks - Tadele A. Abose; Venumadhav Tekulapally; Samuel T. Daka; Diriba C. Kejela; Alemayehu E. Duguma; Desalegn T. Degaga (IEEE Access)
This study introduces an enhanced version of the PEGASIS algorithm, termed the improved energy efficient anytime optimistic (IEE AO) protocol, designed to improve energy efficiency in wireless sensor networks (WSNs). The primary goals are to optimize chain formation, balance energy consumption, and extend the network’s lifespan. The proposed IEE AO algorithm is compared with several existing models, including low energy adaptive clustering hierarchy (LEACH), stable election protocol (SEP), ant colony optimization (ANT), and anytime optimistic (AO) algorithms, under both MAX energy and sequential energy criteria. Simulations conducted across different node densities and chain formation techniques reveal that IEE AO significantly outperforms state-of-the-art algorithms. Specifically, the sequential IEE AO achieves the best performance in terms of network scalability, stability, lifetime, and packet throughput to the base station (BS), requiring only 20 iterations. Among MAX-based algorithms, MAX IEE AO surpasses AO and ANT-based PEGASIS, which require over 200 iterations. The results highlight the effectiveness of the IEE AO algorithm in enhancing energy efficiency, extending network lifetime, improving node retention, and optimizing chain lengths with minimal iterations, making it a suitable solution for both homogeneous and heterogeneous WSNs. The proposed algorithm demonstrates a 40% improvement across all evaluated features compared to existing algorithms.